Influence of Heat Treatment on Ratcheting Fatigue Behavior and Post Ratcheting Tensile Properties of Commercial Aluminum - Kreethi R.; Verma P.; Dutta K. (My University, 2025)
The objective of this work is the study of ratcheting fatigue behavior and post fatigue tensile properties of the commercial aluminum via heat treatment like annealing and normalizing. In view of this, stress controlled fatigue tests carried out at room temperature up to 150 cycles under different combinations of mean stress and stress amplitude using a servo-hydraulic testing machine. It is found that in both annealed and normalized conditions, accumulation of ratcheting strain increases with increasing stress parameters. Strain accumulation in normalized condition is less due to increased dislocation density during asymmetric cyclic loading. In normalized, the saturation in strain accumulation was also achieved earlier as compared to annealed due to attainment of stable dislocation configuration. It has been noticed that the Post fatigue tensile strength enhances while the ductility decreases with increasing stress parameters because of cyclic hardening. Fractographic studies have demonstrated that dimple size decreases with increasing strain accumulation. © 2014, The Indian Institute of Metals - IIM.